A candidate gene approach of the calcineurin pathway to identify variants associated with clinical outcomes in renal transplantation. (March 2016) - Pouché, Lucie; Koitka, Matthias; Stojanova, Jana; Woillard, Jean-Baptiste; Monchaud, Caroline; Villeneuve, Claire; Essig, Marie; Abraham, Julie; Le Meur, Yannick; Rerolle, Jean-Phillippe; Kamar, Nassim; Rostaing, Lionel; et al.
Aim: To investigate the potential influence of variants in genes involved in the calcineurin pathway on the efficacy and toxicity of calcineurin inhibitors in renal transplantation.Materials & methods: Twenty-three polymorphisms in thirteen genes were tested in 381 renal transplant recipients receiving ciclosporin (n = 221) or tacrolimus (n = 160) and mycophenolate mofetil. Data were collected prospectively over the first year post-transplantation.Results: Multivariate survival analyses revealed no genetic associations with biopsy proven acute graft rejection and serious infections. Donor–recipient Cytomegalovirus mismatch was the only variable associated with serious infection.Conclusion: This large exploratory study casts doubts on the potential interest of genetic biomarkers related to CNI pharmacodynamics but associations with other phenotypes in transplantation deserve further studies.